2004
DOI: 10.1023/b:jobb.0000023620.42653.b7
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Palmitic Acid/Ca2+Complexes in the Mitochondrial Membrane: A Possible Role in the Cyclosporin-Insensitive Permeability Transition

Abstract: A possible role of palmitic acid/Ca2+ (PA/Ca2+) complexes in the cyclosporin-insensitive permeability transition in mitochondria has been studied. It has been shown that in the presence of Ca2+, PA induces a swelling of mitochondria, which is not inhibited by cyclosporin A. The swelling is accompanied by a drop in membrane potential, which cannot be explained only by a work of the Ca2+ uniporter. With time, the potential is restored. Evidence has been obtained indicating that the specific content of mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…On the other hand, in the absence of P i and other triggers of the Ca 2+ dependent pore, palmitic acid (and other long chain saturated fatty acids) were recently found to induce opening of a pore insensitive to CsA [13 15]. And we have shown that this is accompanied by recovery of ∆ψ on the inner mitochondrial membrane practically to the ini tial level [15]. Thus, the palmitate induced pore is short living and can close spontaneously [13].…”
mentioning
confidence: 62%
“…On the other hand, in the absence of P i and other triggers of the Ca 2+ dependent pore, palmitic acid (and other long chain saturated fatty acids) were recently found to induce opening of a pore insensitive to CsA [13 15]. And we have shown that this is accompanied by recovery of ∆ψ on the inner mitochondrial membrane practically to the ini tial level [15]. Thus, the palmitate induced pore is short living and can close spontaneously [13].…”
mentioning
confidence: 62%
“…It is known that lipid pores can heal spontaneously [46]. Earlier, we showed that in sucrose/mannitol medium, formation of palmitate/Ca 2+ -induced pores in mitochondria was accompanied by a drop in membrane potential followed by gradual recovery to nearly the initial level [7]. However, mitochondria did not restore their volume, which would require removal of impermeant osmotic agents (sucrose and mannitol) from the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 98%
“…Fatty acids are substrates for mitochondrial respiration, uncouplers of oxidative phosphorylation, inducers of the mitochondrial permeability transition (MPT) pore and pro-apoptotic agents [15]. In the presence of Ca 2+ , long-chain saturated fatty acids also open a cyclosporin A (CsA)-insensitive pore in the mitochondrial inner membrane [6, 7]. Palmitate/Ca 2+ also induces pores in erythrocyte membranes, artificial lipid vesicles, and black lipid membranes [711].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-chain fatty acids that are routinely present in plasma of normal individuals were shown to have cytotoxic effects at high concentrations, impair ATP generation, uncouple OXPHOS, inhibit the respiratory chain, depolarize mitochondria by their protonophoric properties, induce oxidative stress, and have permeability transition. [44][45][46][47][48][49] Medium-chain fatty acid effects on mitochondrial functions are less studied, but may similarly affect mitochondrial respiration and disturb the translocation of ADP in mitochondria. 50 Therefore, it is feasible that the fatty acids that accumulate in tissues of patients with MCAD and LCHAD deficiencies (Table 3) may similarly induce cellular toxicity.…”
Section: Disruption Of Mitochondrial Homeostasis In Mcad and Lchad Dementioning
confidence: 99%